2016
DOI: 10.1007/s11655-016-2523-0
|View full text |Cite
|
Sign up to set email alerts
|

Allicin improves cardiac function by protecting against apoptosis in rat model of myocardial infarction

Abstract: Allicin appears to exert a cardioprotective effect that may be linked to blocking Bcl-2/Bax signaling pathway-denpendent apoptosis, further improving cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Allicin is isolated from garlic and may also be extracted as a brownish orange dry resin from the Garcinia hanburyi tree occurring in South-East Asia (11,12). In previous years, Asians have used allicin as a traditional medicine for the therapy of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Allicin is isolated from garlic and may also be extracted as a brownish orange dry resin from the Garcinia hanburyi tree occurring in South-East Asia (11,12). In previous years, Asians have used allicin as a traditional medicine for the therapy of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Allicin has been shown to exert a wide range of biological effects, including antioxidant activity, the inhibition of platelet activation, antitumor activity, and antimicrobial activity [ 9 – 12 ]. Our previous studies in rats found that allicin mitigates ischemic injury via inhibiting apoptosis [ 13 ]. It was also shown to prevent against myocardial apoptosis and fibrosis in a streptozotocin-induced diabetic models in rats [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is an important physiological process that supports biological life and normal activities (23). If the signal transmission pathways that control and regulate apoptosis are severely disrupted, this causes a number of human diseases, including cancer and infectious diseases (24).…”
Section: Discussionmentioning
confidence: 99%